Analysis of the Need for Interactive Multimedia Development Using Canva in Pressure Material in Grade IX Junior High School - Oktaria, Sely; Susanti, Rahmi; Suratmi, Suratmi (FKIP - Universitas Riau, 2025)
This needs analysis study aims to identify the urgency of developing Canva-assisted interactive multimedia on pressure material in Grade IX at SMP Negeri 4 Lalan, as an effort to improve the quality of science learning. The main problem found is the low mastery of pressure concepts by students (score of 30%) due to conventional learning methods that rely on lectures and static media, making it difficult for students to visualise abstract concepts. The results of the study show a very clear gap between current learning practices and the needs of students and teachers. Students showed a very high urgency for interactive media (95% media need; 100% interactive preference) that contained animations, simulations, and supported self-paced learning. Teachers also had critical awareness of learning constraints (score of 93%) and were in dire need of concept visualisation media (score of 100%). Supported by the readiness of school technology facilities and teachers' enthusiasm for Canva as an easily accessible design platform with the potential to produce interactive media (score of 100%), the development of Canva-based interactive multimedia is a much-needed strategic step to improve students' conceptual understanding and learning motivation in pressure-related material.